An isotopic assay for NADPH oxidase activity and some characteristics of the enzyme from human polymorphonuclear leukocytes. - DeChatelet, L R (1975)
An isotopic assay for NADPH ixodase that measures the amount of NADP formed by the 6-phosphogluconate dehydrogenase reaction has been developed. Under appropriate conditions, the amount of NADP present is directly proportional to the amount of 14CO2 released from [1-14C]6-phosphogluconic acid. Because this assay employs radioisotopes, it is far more sensitive than conventional assays for the enzyme. The human granule NADPH oxidase, as measured by this assay, is active in the presence of CN minus, is stimulated by Mn-2+, and has a pth optimum of 5.5. Granules isolated from cells that have been allowed to ingest zymosan consistently exhibited more enzyme activity than did granules isolated from either resting cells or cells challenged with zymosan that was not preopsonized. This effect was observed over a wide range of substrate concentrations and could not be explained by differences in protein concentrations between the various samples. If whole homogenates are used in place of isolated granules, the enzyme activity can be observed only with a homogenate of phagocytizing cells and even then only at a high concentration of NADPH. This suggests that an inhibitor of the enzyme might be present within the cell. One patient with chronic granulomatous disease was studied. There was no difference in tnadph oxidase activity of the patients' cells when granules from resting and phagocytizing cells were compared. In contrast, the enzyme activity in granules from two control patients doubled upon phagocytosis. These results are consistent with a role for NADPH oxidase in the initiation of the respiratory burst accompanying phagocytosis by human neutrophils.